The Use of Canva in Indonesian Language Learning in Grade 6 at State Elementary School 1 Locondong - Yuliawan, Wahyu; Aryani, Ine Kusuma (UM Purwokerto Press, 2025)
This research investigates the use of the Canva platform in the classroom. With the advancement of technology, there is a pedagogical shift and adaptive learning. The research method employed is a case study approach combined with qualitative analysis techniques to examine a student-centered approach involving participants and collaborative Indonesian language learning through projects. We use a narrative literature review to define learning that leverages technology-based learning resources, ensuring coherence, accessibility, and quality. This research concludes by envisioning that Indonesian language learning will utilize technology in the form of the Canva platform to enhance creative thinking skills, create inclusive, collaborative, and transformative learning experiences.